Overview of Long-Term Contraceptive Method Selection in Post-Section Caesarea in Tabanan Regional General Hospital - Ni Wayan Yuriani; Ni Komang Erny Astiti; Regina Tedjasulaksana (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
Family planning aims to regulate birth of children, ideal birth distance and age, regulate pregnancy, through promotion, protection and assistance according reproductive rights to create a quality family. This research determined overview of the choice of long-term contraceptive methods in post caesarean section at Tabanan Regional Hospital. The design used descriptive observationalÂ  and conducted at Tabanan Regional Hospital on 28 September â€“ 10 November 2024 with 40 respondents post caesarean section days 0-7. Primary data was taken using questionnaire. The results is 72.5% respondents were aged 20-35 years (60.0% of whom chose MKJP), 50.0% had secondary education (40.0% of whom chose MKJP), 55.0% were multipara (50,0% of them chose MKJP), 50.0% had good knowledge (all of them chose MKJP) and 70.0% had husband support (all of them chose MKJP). It is hoped this research can increase the coverage of MKJP among post-cesarean section mothers at Tabanan Regional Hospital by providing effective counseling/education so high rate of caesarean section deliveries can be offset by increasing rate of MKJP uses. It is recommended that hospitals increase the coverage of long-term contraceptive methods for post-cesarean mothers by providing effective and targeted health education/counseling using attractive media.